Fenofibrate Induces Ketone Body Production in Melanoma and Glioblastoma Cells - Grabacka, Maja M.; Wilk, Anna; Antonczyk, Anna; Banks, Paula; Walczyk-Tytko, Emilia; Dean, Matthew; Pierzchalska, Malgorzata; Reiss, Krzysztof (Frontiers in Endocrinology, 2016)
Ketone bodies (beta-hydroxybutyrate, bHB, acetoacetate) are mainly produced in the liver during prolonged fasting or starvation. bHB is a very efficient energy substrate for sustaining ATP production in peripheral tissues; importantly its consumption is preferred over glucose. However, the majority of malignant cells, particularly cancer cells of neuroectodermal origin such as glioblastoma, are not able to use ketone bodies as a source of energy. Here, we report a novel observation that fenofibrate, a synthetic peroxisome proliferator-activated receptor alpha (PPARa) agonist, induces bHB production in melanoma and glioblastoma cells, as well as in neurospheres composed of nontransformed cells. Unexpectedly, this effect is not dependent on PPARa activity or its expression level. The fenofibrate-induced ketogenesis is accompanied by growth arrest and down-regulation of transketolase, but the NADP/NADPH and GSH/GSSG ratios remain unaffected. Our results reveal a new, intriguing aspect of cancer cell biology and highlight the benefits of fenofibrate as a supplement to both canonical and dietary (ketogenic) therapeutic approaches against glioblastoma.